2011
DOI: 10.3141/2241-03
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of Highway Safety Manual Predictive Models for Oregon State Highways

Abstract: The recently released Highway Safety Manual (HSM) published by AASHTO provides a comprehensive set of tools for evaluating and identifying opportunities to improve safety for highway facilities. Included in the HSM is a quantitative method for predicting crashes on the basis of recently developed scientific approaches. These predictive methods currently exist for three facility types: rural two-lane roads; rural multilane highways; and urban and suburban arterial highways. To enhance precision, each HSM predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 2 publications
1
32
0
1
Order By: Relevance
“…Shortly after the release of the HSM, Xie et al calibrated the HSM models for the state of Oregon with the method outlined in the HSM (1). The calibration calculations resulted in factors consistently below the expected value of 1.0, an outcome that was likely attributed to Oregon's property damage only crash self-reporting procedures and its higher property damage only reporting thresholds compared with the states that were used in developing the HSM crash proportions (1).…”
Section: Calibration Effortsmentioning
confidence: 97%
“…Shortly after the release of the HSM, Xie et al calibrated the HSM models for the state of Oregon with the method outlined in the HSM (1). The calibration calculations resulted in factors consistently below the expected value of 1.0, an outcome that was likely attributed to Oregon's property damage only crash self-reporting procedures and its higher property damage only reporting thresholds compared with the states that were used in developing the HSM crash proportions (1).…”
Section: Calibration Effortsmentioning
confidence: 97%
“…In particular, the HSM predictive method was assumed as a benchmark by several studies, which calibrated it for different areas [42][43][44][45][46][47][48]. Some of them clearly concluded that locally-derived functions fits better data than the calibration of other functions.…”
Section: Transferability Of Predictive Methodsmentioning
confidence: 99%
“…Calibration factors are the third component of the HSM predictive method. Numerous researchers have updated the calibration factors for their respective jurisdictions (Banihashemi, 2011;Fitzpatrick, Schneider, & Carvell, 2006;Mehta, & Lou, 2013;Persaud, Lord, & Palmisano, 2002;Shin, Lee, & Dadvar, 2014;Sun, Magri, Shirazi, Gillella, & Li, 2011;Xie, Gladhill, Dixon, & Monsere, 2011). Researchers have found that calibration factors may vary not only across different parts of a region, but also based on geometric characteristics (for instance, tangent versus horizontal curve segments) (Fitzpatrick, Schneider, et al, 2006).…”
Section: Introductionmentioning
confidence: 99%